Проблемы трансдисциплинарности и роль информатики - Палагин, А.В. (Кибернетика и системный анализ, 2013)
Запропоновано та проаналізовано деякі методи і засоби інформаційно-технологічної підтримки трансдисциплінарних наукових досліджень в їх становленні та розвитку. Зроблено акцент на онтолого-керовані сервіс-орієнтовані системи представлення знань в глобальному мережевому середовищі. Risk factors of coronary artery tortuosity were identified using binary logistic regression. Some methods and means of information-technological support of transdisciplinary scientific researches are proposed and reviewed during their formation and development. Emphasis is placed on ontology-driven service-oriented systems of knowledge representation in a global network environment. F